Silicon-based negative electrode active material and manufacturing method thereof
By coating a coating layer of amorphous carbon on the surface of the silicon-based negative electrode active material, the capacity deterioration caused by volume changes during charging and discharging of the silicon-based material is solved, and excellent cycle life and capacity retention rate are achieved.
Patent Information
- Application Number
- CN202380066959.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-01
- Filing Date
- 2023-07-27
- Publication Date
- 2025-04-25
AI Technical Summary
The silicon-based negative electrode active material causes crystal structure changes and volume changes when the alloy is electrochemically formed with lithium, resulting in deterioration of the capacity of the secondary battery.
A specific Raman spectral ratio relationship (1 < R1/R2 < 3) is satisfied by coating a coating layer of amorphous carbon on the surface of the porous silicon-based material to suppress volume changes during charging and discharging.
It effectively suppresses the volume change of the negative electrode and significantly improves the cycle life characteristics and battery capacity retention rate of the secondary battery.
Smart Images

Figure CN119895591A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a silicon-based negative electrode active material and a method for manufacturing the same, and more particularly, to a silicon-based negative electrode active material that can provide excellent capacity retention by effectively suppressing the volume change of silicon during the charge / discharge process of a secondary battery and a method for manufacturing the silicon-based negative electrode active material. Background Art
[0002] In recent years, the demand for secondary batteries having improved life characteristics allowing long-term use and high energy density performance is increasing in various industrial fields such as electric or hybrid vehicles and aerospace and portable electronic devices.
[0003] Generally, graphite is mainly used as a representative negative electrode material contained in a negative electrode of a secondary battery composed of a positive electrode, a negative electrode, an electrolyte, and a separator and commercially used, but graphite has a capacity per unit mass of only 372 mAh / g.
[0004] For example, negative electrode active materials such as silicon, tin, and oxides thereof that electrochemically form alloys with lithium, which show higher capacity than graphite, show high capacity of about 1000 mAh / g or more, and in particular, since the theoretical maximum capacity of silicon is 4200 mAh / g and the theoretical maximum capacity of silicon oxide is 1500 mAh / g, research aimed at using silicon-based materials as negative electrode materials is being actively conducted.
[0005] However, when the silicon-based negative electrode active material is electrochemically alloyed with lithium, the crystal structure changes and the volume changes by 300% or more. In this case, defects such as physical peeling or increased contact resistance between the negative electrode active materials or between the negative electrode active materials and the current collector occur during charging and discharging, which rapidly leads to the degradation of the secondary battery capacity as the charge / discharge cycle proceeds.
[0006] To solve this problem, a technology has been proposed to nanosize silicon into a wire shape or the like and composite it with a carbon material, but initial charge and discharge efficiency, cycle characteristics, high rate properties, etc. are still reduced, making commercialization difficult.
[0007] Therefore, for higher capacity of secondary batteries, there is a need to develop silicon-based negative electrode active materials showing excellent capacity retention and improved cycle-life characteristics by effectively controlling volume change. Summary of the invention
[0008] Technical issues
[0009] An object of the present invention is to provide a negative electrode active material having excellent battery capacity and excellent cycle life characteristics.
[0010] Another object of the present invention is to provide a method for manufacturing a negative electrode active material, which can effectively suppress the volume change of the negative electrode during the charge and discharge process.
[0011] Technical Solution
[0012] In one general aspect, a negative electrode active material includes: a core comprising a porous silicon-based material; and a coating layer comprising amorphous carbon coated on a surface of the core, wherein the coating layer satisfies the following Relationship 1:
[0013] (Equation 1)
[0014] 1 <R1 / R2<3
[0015] Where R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band is G The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength of 1350±20cm -1 The peak center of the G band is located at 1580±20cm -1 The peak center is within the wave number range of 1500±10cm -1 The peak center within the wavenumber range.
[0016] In the negative active material according to the exemplary embodiment of the present invention, amorphous carbon may be obtained from a resin having a repeating unit including an arylene group.
[0017] In the negative active material according to the exemplary embodiment of the present invention, the resin may have a repeating unit including one or more phenolic hydroxyl groups.
[0018] In the negative active material according to the exemplary embodiment of the present invention, the hydroxyl group equivalent contained in the resin may be 150 g / eq to 300 g / eq.
[0019] In the negative active material according to the exemplary embodiment of the present invention, R1 may be 0.9 to 1.05.
[0020] In the negative active material according to the exemplary embodiment of the present invention, R2 may be 0.5 to 0.6.
[0021] In the negative electrode active material according to the exemplary embodiment of the present invention, the silicon-based material may include silicon (Si), silicon oxide (SiOx (0 < x ≤ 2)), at least one material selected from silicon alloys or combinations thereof.
[0022] In the negative electrode active material according to an exemplary embodiment of the present invention, the silicon-based material may contain 30 at% or more of silicon having an oxidation number of 4 in the Si 2P XPS spectrum of the negative electrode active material, and the Si 2P XPS spectrum includes deconvoluted peaks corresponding to silicon having oxidation numbers of 0, 1, 2, 3, and 4.
[0023] In the negative electrode active material according to an exemplary embodiment of the present invention, the silicon-based material may satisfy the following relationship 2:
[0024] (Relationship 2)
[0025] A4 / A1 ≥ 4
[0026] Wherein, in the Si 2P XPS spectrum of the negative electrode active material, A4 is the atomic percentage (atom%) of silicon having an oxidation number of 4, and A1 is the atomic percentage of silicon having an oxidation number of 1.
[0027] In the negative electrode active material according to an exemplary embodiment of the present invention, the coating layer may have a thickness of 5 nm to 30 nm.
[0028] In the negative electrode active material according to an exemplary embodiment of the present invention, the core may have an average diameter of 0.1 μm to 50 μm.
[0029] In another general aspect, a negative electrode for a secondary battery includes the above negative electrode active material.
[0030] In yet another general aspect, a method for manufacturing a negative electrode active material is provided.
[0031] The method for manufacturing a negative electrode active material according to the present invention may include: a) preparing a coating solution containing a resin having a repeating unit containing an arylene group and a solvent for forming a coating layer containing amorphous carbon; b) preparing a first mixture of porous silicon-based powder in the coating solution; and c) drying the first mixture and then performing heat treatment.
[0032] In the method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention, the coating solution may have a viscosity of 5 cP to 200 cP.
[0033] In the method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention, the weight ratio of the coating solution to the silicon-based powder may be 1:8 to 1:15.
[0034] In the method for manufacturing a negative active material according to the exemplary embodiment of the present invention, the resin included in the coating solution may have a repeating unit including one or more phenolic hydroxyl groups.
[0035] In the method for manufacturing a negative electrode active material according to the exemplary embodiment of the present invention, the heat treatment of c) may be performed under a temperature condition of 900° C. to 1100° C. under an inert gas atmosphere.
[0036] In the method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention, a unit process can be performed one or more times using the product obtained after the heat treatment in c), and the unit process includes: b-1) preparing a second mixture of the product in a coating solution; and c-1) drying the second mixture and then heat-treating it.
[0037] In the method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention, in the first coating layer of the product obtained after c) to the Nth coating layer of the product obtained by performing the unit process n times or more, the standard deviations of R1 values and R2 values from the first coating layer to the Nth coating layer may be less than 0.1, respectively.
[0038] In this paper, R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band is G The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength of 1350±20cm -1 The peak center of the G band is located at 1580±20cm -1 The peak center is within the wave number range of 1500±10cm -1 The peak center within the wavenumber range.
[0039] Beneficial Effects
[0040] The negative electrode active material according to the exemplary embodiment of the present invention includes a core including a porous silicon-based material and a coating layer including amorphous carbon coated on the surface of the core, and since the coating layer satisfies the following Relationship 1, the discharge capacity is excellent and the volume change of the negative electrode occurring during the charging and discharging process is effectively suppressed, thereby providing significantly improved cycle life characteristics:
[0041] (Equation 1)
[0042] 1 <R1 / R2<3
[0043] Where R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band is G The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength of 1350±20cm -1 The peak center of the G band is located at 1580±20cm -1 The peak center is within the wave number range of 1500±10cm -1 The peak center within the wavenumber range. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a graph showing the results of X-ray diffraction (XRD) analysis of a negative electrode active material prepared according to an exemplary embodiment.
[0045] Figure 2 is a diagram showing a transmission electron microscope (TEM) image of a negative electrode active material prepared according to an exemplary embodiment.
[0046] Figure 3 (a) and Figure 3 (b) is a graph showing Raman spectra measured for each of the carbon coating layers included in the negative electrode active materials of Comparative Examples 1 and 2 and Examples 1 to 3, and results of Raman spectra showing deconvoluted peaks fitted from the measured Raman spectra.
[0047] Figure 4 (a) Figure 4 (b) and Figure 4 (c) is a graph showing high-resolution Si 2PXPS spectra including deconvoluted peaks corresponding to silicon having oxidation numbers of 0, 1, 2, 3, and 4 for the negative electrode active materials of Example 1 and Comparative Examples 1 and 2, respectively.
[0048] Figure 5 (a) and Figure 5 (b) are graphs showing high-resolution C1s XPS spectra of negative electrode active materials prepared according to Example 1 and Comparative Example 2, respectively.
[0049] Figure 6 (a) and Figure 6(b) are graphs respectively showing the results of charge and discharge cycle-life characteristics and rate performance of a battery including a negative electrode active material prepared according to an exemplary embodiment. DETAILED DESCRIPTION
[0050] Hereinafter, a negative active material according to an exemplary embodiment of the present invention will be described in detail with reference to the accompanying drawings. The accompanying drawings provided below are provided by way of example so that the spirit of the present invention can be fully conveyed to those skilled in the art.
[0051] Therefore, the present invention is not limited to the drawings provided below, but can be embodied in many different forms, and the drawings suggested below can be exaggerated to illustrate the spirit of the present invention. Unless otherwise defined, the technical terms and scientific terms used herein have the general meanings commonly understood by those skilled in the art to which the present invention belongs, and descriptions of known functions and configurations that may unnecessarily obscure the gist of the present invention will be omitted in the following description and drawings.
[0052] In addition, unless the context indicates otherwise, singular forms used in the specification and the appended claims may be intended to include plural forms as well.
[0053] In this specification and the appended claims, terms such as first, second, and Nth are not used in a limiting sense, but are used for the purpose of distinguishing one constituent element from other constituent elements.
[0054] In this specification and the appended claims, terms such as “including” or “having” mean that the characteristics or constituent elements described in the specification are present, and do not preclude the possibility of adding one or more other characteristics or constituent elements unless otherwise specifically limited.
[0055] In the present specification and the appended claims, when a part such as a layer (film), a region and a constituent element exists on another part, it includes not only the case where the part is in contact with the other part and directly located on the other part, but also the case where other layers (films), other regions, other constituent elements, etc. are interposed between these parts.
[0056] The negative electrode active material according to an exemplary embodiment of the present invention includes: a core including a porous silicon-based material; and a coating layer including amorphous carbon coated on a surface of the core, wherein the coating layer coated on the surface of the core satisfies the following Relationship 1:
[0057] (Equation 1)
[0058] 1 <R1 / R2<3
[0059] Where R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band isG The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength of 1350±20cm -1 The G band has a peak center located at 1600±20cm -1 The peak center is within the wave number range of 1500±10cm -1 The peak center within the wavenumber range.
[0060] The negative electrode active material according to an exemplary embodiment of the present invention includes a silicon-based material, but is provided with a coating layer containing amorphous carbon coated on the surface of the core, the coating layer having the above-mentioned Raman characteristics, and therefore, unlike conventional silicon-based negative electrode active materials, the volume change of the silicon-based material during charging and discharging is effectively suppressed, thereby having excellent cycle life characteristics.
[0061] In addition, since the coating layer is uniformly disposed on the surface of the core comprising the porous silicon-based material, the conductive properties of the surface of the negative electrode active material can be improved. In this article, the coating layer uniformly disposed on the surface of the core may include a coating layer disposed inside the pores contained in the porous silicon-based material.
[0062] As an exemplary embodiment, the amorphous carbon included in the coating layer may be obtained from a resin having a repeating unit including an arylene group.
[0063] As a specific example, the arylene group included in the resin may be a C6 to C20 arylene group, and hydrogen of the arylene group may be substituted with a C1 to C4 alkyl group. The arylene group may specifically be a phenylene group.
[0064] As a specific example, the resin having a repeating unit containing an arylene group may have a repeating unit containing a phenolic hydroxyl group, and the hydroxyl group equivalent contained in the resin may be 100 g / eq to 500 g / eq, specifically 150 g / eq to 300 g / eq, and more specifically 200 g / eq to 250 g / eq.
[0065] In particular, in the method for manufacturing a negative electrode active material described later, a resin having the above-mentioned characteristics and a solvent are contained in a coating solution, and after the coating solution is mixed with a porous silicon-based material, the resin is formed into a coating layer containing amorphous carbon by a heat treatment process, and the coating layer is coated on the surface of the core containing the porous silicon-based material. In this article, since the resin contained in the coating solution satisfies the above-mentioned characteristics, the coating layer is uniformly placed on the surface of the core containing the porous silicon-based material, and the above-mentioned Raman characteristics can also be satisfied. The resin will be described in detail from the perspective of the method for manufacturing a negative electrode active material described later.
[0066] As specific examples, the coating layer including amorphous carbon may have a thickness of 5 nm to 50 nm, substantially 5 nm to 30 nm, more substantially 5 nm to 15 nm, and still more substantially 8 nm to 12 nm.
[0067] In order to effectively suppress the volume change of the core including the porous silicon-based material and also to improve the conductive properties of the surface of the negative electrode active material, it is favorable for the thickness of the coating layer including amorphous carbon to satisfy the above range.
[0068] As an example, the negative active material may include 1.5 wt % to 20 wt % of amorphous carbon, specifically 1.8 wt % to 15 wt % of amorphous carbon, and more specifically 2.0 wt % to 10 wt % of amorphous carbon.
[0069] In this article, amorphous carbon can be any carbon that satisfies 0.5 D1 / I G Raman characteristics of carbon in the range of <1.2, I D1 / I G The Raman spectrum has a wavelength at 1350 cm -1 The central peak intensity of the D1 band near the peak I D1 With a position of approximately 1580cm -1 The central peak intensity of the G band in the region of the peak I G The ratio (I D1 / I G ).
[0070] Generally, in the Raman spectrum of carbon-based materials, the central peak of the D1 band is a peak that appears due to the disorder of sp2 carbon, and due to the existing defects, the higher the central peak intensity of the D1 band, the lower the crystallinity, and the lower the central peak intensity of the D1 band, the higher the crystallinity.
[0071] In a specific example, the coating layer including amorphous carbon may satisfy the following Relationship 1:
[0072] (Equation 1)
[0073] 1 <R1 / R2<3
[0074] Where R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band is G The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength of 1350±20cm -1 The peak center of the G band is located at 1580±20cm -1 The peak center is within the wave number range of 1500±10cm -1 The peak center within the wavenumber range.
[0075] Herein, the central peak of the D1 band, the central peak of the D3 band, and the central peak of the G band are fitted from the obtained Raman spectrum, but may be deconvoluted peaks corresponding to each of the above wavenumber ranges.
[0076] In particular, since the coating layer containing amorphous carbon satisfies the above-mentioned Raman characteristics and is uniformly placed on the surface of the core containing the porous silicon-based material, the volume change of the porous silicon-based material contained in the negative electrode active material is effectively suppressed, and the conductive performance of the surface of the negative electrode active material can also be improved.
[0077] As specific examples, Relationship 1 (R1 / R2) may be 1.3 or greater, 1.4 or greater, 1.5 or greater, or 1.6 or greater, and substantially 2.5 or less, 2.3 or less, 2.0 or less, or 1.9 or less.
[0078] As an exemplary embodiment, R1 may be 0.87 to 1.10, specifically 0.9 to 1.05, and more specifically 0.93 to 1.02, and R2 may be 0.45 to 0.65, specifically 0.5 to 0.6, and more specifically 0.52 to 0.59.
[0079] In an exemplary embodiment, the coating layer including amorphous carbon may include carbon having a C-C bond structure, a C-O bond structure, a C=O bond structure, and an O-C=O bond structure. Herein, the carbon having the above bond structure may be obtained from a high-resolution C1s XPS spectrum of the negative active material measured using an X-ray photoelectron spectroscopy (XPS).
[0080] As a specific example, a coating layer containing amorphous carbon may contain 65 at% or more, 66 at% or more, or 67 at% or more of carbon having a C-C bond structure, and substantially contain 80 at% or less of carbon having a C-C bond structure. Thus, the negative electrode active material containing carbon having a C-C bond structure within the above range can improve the conductivity on the surface of the negative electrode active material. 2 bond structure carbon. That is, the negative electrode active material having a C-C bond structure within the above range can improve the conductivity on the surface of the negative electrode active material.
[0081] As a specific example, the ratio (C2 / C1) of at% (C2) of carbon having a C-C bond structure to at% (C1) of carbon having an O-C=O bond structure may be 10 or greater, 11 or greater, 12 or greater, 12.5 or greater, and substantially 15 or less.
[0082] As an exemplary embodiment, a core containing a porous silicon-based material coated with the above coating layer containing amorphous carbon may be granular, and the granular core may have an average diameter of 0.1 μm to 50 μm, particularly may have an average diameter of 0.5 μm to 30 μm, and more particularly may have an average diameter of 0.5 μm to 20 μm. Herein, the average diameter of the core may be the particle diameter at 50% of the particle size distribution of the granular core, and the core may be a single particle formed of a porous silicon-based material, and of course may include an aggregate of single particles.
[0083] The porous silicon-based material contained in the core may have a Brunauer-Emmett-Teller (BET) specific surface area of 0.5 m 2 / g to 20 m 2 / g, particularly may have a BET specific surface area of 1 m 2 / g to 10 m 2 / g, and more particularly may have a BET specific surface area of 1 m 2 / g to 5 m 2 / g.
[0084] As an exemplary embodiment, the silicon-based material contained in the core may include at least one material selected from silicon (Si), silicon oxide (SiO x (0 < x ≤ 2)), silicon alloy, and combinations thereof, and the silicon alloy may include, for example, materials selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements other than Si, transition metals, rare earth elements, or combinations thereof.
[0085] Herein, silicon-based materials such as silicon, silicon oxide, and silicon alloy may include amorphous silicon, crystalline silicon, or a mixed form thereof, and the porous silicon-based material may particularly be silicon oxide (SiO x, x is greater than 0 and less than 2), and more particularly may be a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, but the present invention is not limited thereto.
[0086] As non-limiting examples, the doping element may be selected from one or more of lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn), and bismuth (Bi).
[0087] As a specific example, the silicon-based material may contain 30 at % or more of silicon having an oxidation number of 4 in the Si 2P XPS spectrum of the above negative active material, the Si 2P XPS spectrum including deconvoluted peaks corresponding to silicon having oxidation numbers of 0, 1, 2, 3, and 4.
[0088] Herein, the peak corresponding to silicon with an oxidation number of 0 among the deconvoluted peaks included in the Si 2P XPS spectrum may be a peak located in a binding energy range of 98 eV to 100 eV, and the peaks corresponding to silicon with oxidation numbers of 1, 2, 3, and 4 may refer to peaks located in binding energy ranges of 100.5 eV to 101.5 eV, 101.6 eV to 102.5 eV, 102.6 eV to 103.5 eV, and 103.6 eV to 104.5 eV, respectively.
[0089] In addition, a peak located within the above-mentioned binding energy range means that the position of the maximum intensity value in the corresponding peak is within the binding energy range.
[0090] As a favorable example, the silicon-based material may contain 30at% or more, 35at% or more, 36at% or more, 37at% or more, 38at% or more, 39at% or more or 40at% or more and substantially 60at% or less and more substantially 55at% or less of silicon having an oxidation number of 4 in the Si 2P X-ray photoelectron spectroscopy (XPS) spectrum of the above-mentioned negative electrode active material.
[0091] In a negative electrode active material comprising a silicon-based material on which a coating layer comprising amorphous carbon is coated, since the silicon-based material contains silicon with an oxidation number of 4 in the Si 2P X-ray photoelectron spectroscopy (XPS) spectrum of the negative electrode active material within the above-mentioned range, the volume change of the silicon-based material is effectively suppressed during charging and discharging, thereby having excellent cycle life characteristics and also providing excellent battery capacity characteristics.
[0092] As a specific example, silicon-based materials may satisfy the following relation 2:
[0093] (Equation 2)
[0094] A4 / A1≥4
[0095] Here, in the Si 2P XPS spectrum of the negative electrode active material, A4 is the atomic percentage of silicon having an oxidation number of 4, and A1 is the atomic percentage of silicon having an oxidation number of 1.
[0096] As an example, in the Si 2P XPS spectrum of the negative electrode active material, the ratio of the atomic percentage of silicon with an oxidation number of 4 to the percentage of silicon with an oxidation number of 1 (A4 / A1) can be 4 or greater, 5 or greater, 6 or greater, 7 or greater, or 8 or greater and substantially 10 or less.
[0097] Since the negative electrode active material contains more silicon with an oxidation number of 4, the battery capacity characteristics can be improved, but since there are limitations in suppressing the volume change during charging and discharging, in order to provide excellent battery capacity characteristics and at the same time more effectively suppress the volume change of the negative electrode during charging and discharging, it is advantageous for the silicon-based material to satisfy Relationship 2.
[0098] The present invention provides a negative electrode for a secondary battery comprising the negative electrode active material.
[0099] In this article, the negative electrode can be a negative electrode of a secondary battery, especially a lithium secondary battery. The negative electrode may include a current collector; and a negative electrode active material layer disposed on at least one surface of the current collector and containing the above-mentioned negative electrode active material, and if necessary, the negative electrode active material layer may also include a binder and a conductive material commonly used in the negative electrode and negative electrode active material for a secondary battery.
[0100] In addition, the present invention includes a secondary battery including the above-mentioned negative electrode. In particular, the present invention includes a lithium secondary battery including the above-mentioned negative electrode. The lithium secondary battery may include: a positive electrode including a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector; the above-mentioned negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte that conducts lithium ions. In this article, since the positive electrode current collector, the negative electrode current collector, the positive electrode active material or the composition of the positive electrode active material layer, the separator, the electrolyte salt concentration of the electrolyte, the electrolyte salt or the solvent, etc. are any materials or compositions commonly used in lithium secondary batteries, the present invention is not limited thereto.
[0101] According to another exemplary embodiment, the present invention provides a method for manufacturing a negative electrode active material.
[0102] A method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention includes: a) preparing a coating solution including a resin having a repeating unit including an arylene group and a solvent for forming a coating layer including amorphous carbon; b) preparing a first mixture of a porous silicon-based powder in the prepared coating solution; c) drying the first mixture and then heat-treating it.
[0103] The negative electrode active material according to the exemplary embodiment of the present invention is manufactured by a simple process of mixing a porous silicon-based powder with a coating solution including a resin having a repeating unit including an arylene group and a solvent to prepare a first mixture, and then drying and heat-treating the first mixture, but a coating layer including amorphous carbon on the surface of the porous silicon-based powder can be formed with a uniform thickness. Herein, the amorphous carbon included in the formed coating layer can be placed inside the pores included in the porous silicon-based powder and on the surface of the porous silicon-based powder.
[0104] Hereinafter, the method for manufacturing a negative electrode active material according to an exemplary embodiment of the present invention will be described in detail for each step.
[0105] First, a) a coating solution containing a resin having a repeating unit containing an arylene group and a solvent is prepared for forming a coating layer containing amorphous carbon.
[0106] Herein, the resin having a repeating unit including an arylene group included in the coating solution may be similar to or the same as described above.
[0107] However, since the resin contained in the coating solution is formed as a coating layer containing amorphous carbon on the surface of the porous silicon-based powder (including pores) through the heat treatment process of step c) described later, as the resin, a resin having a high carbon content, high fluidity and excellent solubility is preferred so as to form a uniform coating layer and to uniformly form the coating layer even for the pores included in the porous silicon-based powder.
[0108] As a favorable example, the arylene group contained in the resin for forming the coating layer containing amorphous carbon can be a C6 to C20 arylene group, particularly a phenylene group, and more particularly, the resin can have a repeating unit containing one or more phenolic hydroxyl groups, and the hydroxyl group equivalent contained in the resin can be 100 g / eq to 500 g / eq, particularly 150 g / eq to 300 g / eq, and more particularly 200 g / eq to 250 g / eq.
[0109] When the hydroxyl equivalent contained in the resin is less than 100 g / eq, the fluidity may decrease, and when the hydroxyl equivalent is greater than 500 g / eq, the uniformity of the coating layer formed after the heat treatment process may deteriorate, and therefore, it is preferred that the hydroxyl equivalent contained in the resin satisfies the above range.
[0110] As a specific example, the resin having a repeating unit including an arylene group may include 75 wt % to 95 wt %, for example 80 wt % to 80 wt % of carbon.
[0111] As described above, since the resin having a repeating unit containing an arylene group can have high fluidity even when containing a high content of carbon, it can be formed into a uniform coating layer on the entire surface of the silicon-based powder and in the pores contained in the porous silicon-based powder through a heat treatment process.
[0112] In exemplary embodiments, a coating solution prepared to form a coating layer including amorphous carbon may include the above-described resin and a solvent.
[0113] Herein, the use of the solvent is not limited as long as the solvent can dissolve the above resin, and as a specific example, the solvent may be one or more polar solvents selected from the group consisting of distilled water, C1 to C5 linear or branched alcohols, acetone, and ethyl acetate.
[0114] As a specific example, a weight ratio of the resin having a repeating unit including an arylene group and the solvent contained in the coating solution may be 1:1 to 1:20, substantially 1:3 to 1:15, and more substantially 1:5 to 1:10.
[0115] For example, the coating solution may have a viscosity of 1 cP to 400 cP, specifically 1 cP to 250 cP, more specifically 2 cP to 200 cP.
[0116] Subsequently, b) a first mixture of porous silicon-based powder in the prepared coating solution is prepared.
[0117] Herein, since the porous silicon-based powder is the same as or similar to the above-mentioned silicon-based material or a core including the silicon-based material, a detailed description thereof will be omitted.
[0118] As an exemplary embodiment, the weight ratio of the coating solution contained in the first mixture to the silicon-based powder may be 1:5 to 1:20, specifically 1:8 to 1:15, and more specifically 1:9 to 1:12. In order to uniformly form a coating layer having a desired thickness on the silicon-based powder through a heat treatment process described later, it is preferred that the weight ratio of the coating solution contained in the first mixture to the silicon-based powder satisfies the above range.
[0119] In an exemplary embodiment, the first mixture in which the coating solution and the silicon-based powder are mixed in the above-mentioned weight ratio can be prepared by stirring for 5 minutes or more, particularly 10 minutes or more, and more particularly 15 minutes or more, and the time for performing the stirring can be substantially 60 minutes or less, and more substantially 30 minutes or less, but the upper limit of the time for performing the stirring is not limited.
[0120] However, when the time of the stirring process is less than 5 minutes, the coating solution is not sufficiently coated on the pores included in the porous silicon-based powder and the surface of the powder, and thus, it is preferable to perform the stirring process during the above period of time.
[0121] Subsequently, c) the prepared first mixture is dried and then heat-treated to prepare a negative electrode active material.
[0122] Herein, through the drying process performed before the heat treatment, the coating solution coated on the porous silicon-based powder is uniformly distributed, and the solvent contained in the coating solution can also be removed.
[0123] As a specific example, the drying process may be performed under a temperature condition of 60 to 150° C., particularly 80 to 130° C., and more particularly 100 to 120° C. for 0.5 to 5 hours, substantially for 1 to 3 hours.
[0124] When the temperature is less than 60°C and / or the execution time is less than 0.5 hour in the drying process performed before the heat treatment, the removal of the solvent contained in the coating solution may not be perfectly performed, and when the temperature is higher than 150°C and / or the execution time is greater than 5 hours, the uniformity of the coating solution placed on the porous silicon-based powder may deteriorate, and therefore, it is preferred to perform the drying process under the above conditions.
[0125] As an exemplary embodiment, the heat treatment performed after drying the prepared first mixture may be performed under an inert gas atmosphere at a temperature of 800° C. to 1300° C., particularly 900° C. to 1100° C. Herein, the inert gas atmosphere may refer to an atmosphere in which, for example, nitrogen, argon, helium, krypton, xenon, etc. are present.
[0126] As a specific example, the porous silicon-based powder having a coating layer containing amorphous carbon formed thereon can be heat-treated within the above temperature range for 0.5 hour to 5 hours, specifically 0.7 hour to 3 hours, and more specifically 0.8 hour to 2 hours, and then naturally cooled to prepare a negative electrode active material.
[0127] Herein, the above-mentioned heat treatment temperature may be achieved at a heating rate of 0.5° C. / min to 10° C. / min, substantially 1° C. / min to 5° C. / min.
[0128] In exemplary embodiments, the properties of the silicon-based powder included in the first mixture may be controlled by the above-described heat treatment process.
[0129] In particular, when the silicon-based powder is silicon oxide, the surface chemical properties of the silicon oxide contained in the negative electrode active material obtained after the heat treatment process can be different from the surface chemical properties of the silicon oxide contained in the first mixture. Herein, the surface chemical properties can be measured by X-ray photoelectron spectroscopy (XPS).
[0130] More specifically, the silicon-based material contained in the negative electrode active material obtained after the heat treatment process may contain 30 at % or more, 35 at % or more, 36 at % or more, 37 at % or more, 38 at % or more, 39 at % or more, or 40 at % or more and substantially 60 at % or less and more substantially 55 at % or less of silicon with an oxidation number of 4 in a Si 2P X-ray photoelectron spectroscopy (XPS) spectrum of the negative electrode active material including deconvoluted peaks corresponding to silicon with oxidation numbers of 0, 1, 2, 3, and 4, and the ratio (A4 / A1) of the atomic percentage of silicon with an oxidation number of 4 to the atomic percentage of silicon with an oxidation number of 1 in the Si 2P XPS spectrum of the negative electrode active material may be 4 or more, 5 or more, 6 or more, 7 or more, or 8 or more and substantially 10 or less.
[0131] Herein, a peak corresponding to silicon having each oxidation number among deconvoluted peaks included in the Si 2P XPS spectrum is similar to or the same as the above description, and a detailed description thereof will be omitted.
[0132] As an exemplary embodiment, using the product obtained after the heat treatment in c), that is, a porous silicon-based powder having a coating layer containing amorphous carbon formed thereon, the unit process can be performed one or more times, wherein the unit process includes: b-1) preparing a second mixture of the product in the prepared coating solution; and c-1) drying the prepared second mixture and then heat-treating it.
[0133] The thickness of the coating layer formed on the surface of the porous silicon-based powder can be easily adjusted according to the number of times the unit process is performed.
[0134] As specific examples, the unit process may be performed one or more times, two or more times, three or more times, four or more times, or five or more times and substantially 50 times or less, more substantially 30 times or less.
[0135] Herein, although the present invention is not limited to the number of times the unit process is performed, it is preferred that the finally formed coating layer satisfies the above-mentioned Raman characteristics (Relation 1).
[0136] As an example, in the first coating layer of the product obtained after step c) to the Nth coating layer of the product obtained by performing the above unit process n times or more, the standard deviations of the R1 value and the R2 value of the first coating layer to the Nth coating layer can be less than 0.5, particularly less than 0.3, and more particularly less than 0.1. Herein, N is a natural number, or a natural number satisfying the condition of 0 < N ≤ 20, particularly 0 < N ≤ 10, more particularly 0 < N ≤ 5, and still more particularly 0 < N ≤ 3.
[0137] Herein, R1 is the ratio (I D1 / I G ) of the central peak intensity I of the D1 band to the central peak intensity I of the G band, and R2 is the ratio (I D1 / I G ) of the central peak intensity I of the D3 band to the central peak intensity I of the G band. In the Raman spectrum, the D1 band has a peak center within the wavenumber range of 1350 ± 20 cm D3 , the G band has a peak center within the wavenumber range of 1580 ± 20 cm G , and the D3 band has a peak center within the wavenumber range of 1500 ± 10 cm D3 . G -1 -1 -1
[0138] Since the negative electrode active material manufactured according to the exemplary embodiment of the present invention includes a coating layer satisfying the above Raman characteristics, although the negative electrode active material includes a silicon-based material, different from a conventional silicon-based negative electrode material, it can effectively suppress the volume change of the silicon-based material during charging and discharging to have excellent cycle life characteristics, and the coating layer containing amorphous carbon is also uniformly disposed on the surface of the negative electrode active material, and thus can improve the conductive performance of the surface of the negative electrode active material.
[0139] Hereinafter, the negative electrode active material according to the exemplary embodiment of the present invention will be described in more detail through the following examples. However, the following examples are only for reference to describe the present invention in detail, and the present invention is not limited thereto and can be implemented in various forms.
[0140] In addition, unless otherwise defined, all technical terms and scientific terms have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used herein are only for effectively describing a certain exemplary embodiment and are not intended to limit the present invention.
[0141] (Example 1)
[0142] 0.2 g of Xylok resin (KOLON Industry) was dissolved in 2 mL of acetone solvent to prepare a coating solution with a concentration of 2 M, and then SiO x (Sigma Aldrich) powder was mixed with the prepared coating solution so that the coating solution and SiO x The weight ratio of the powders was 1:10, and stirring was performed at a speed of 300 rpm for 20 minutes to prepare a mixture.
[0143] Thereafter, the prepared mixture was dried in a vacuum oven at 110°C for 2 hours, heated to 1000°C at a heating rate of 3°C / min under an argon atmosphere, and heat treated for 1 hour to produce a composite material (negative electrode active material) in which a carbon coating layer was formed on the surface of silicon oxide by carbonization of Xylok resin.
[0144] (Example 2)
[0145] In addition to replacing SiO x A composite material having a carbon coating layer formed thereon was manufactured in the same manner as in Example 1, except that the powder was mixed with the coating solution to prepare a mixture and the mixture was dried and then heat-treated as a unit process once.
[0146] (Example 3)
[0147] In addition to replacing SiO x A composite material was manufactured in the same manner as in Example 1, except that the powder was mixed with the coating solution to prepare a mixture and the mixture was dried and then heat-treated as a unit process twice to manufacture a composite material having a carbon coating layer formed thereon.
[0148] (Example 4)
[0149] In addition to replacing SiO x A composite material was manufactured in the same manner as in Example 1, except that the powder was mixed with the coating solution to prepare a mixture and the mixture was dried and then heat-treated three times as a unit process to manufacture a composite material having a carbon coating layer formed thereon.
[0150] (Comparative Example 1)
[0151] SiO x (Sigma-Aldrich) powder itself is applied as the negative electrode active material.
[0152] (Comparative Example 2)
[0153] SiO x(Sigma-Aldrich) powder was added into a chemical vapor deposition (CVD) chamber, and toluene gas was supplied to manufacture a negative electrode active material having a carbon coating layer formed on the surface of the silicon oxide powder.
[0154] (Comparative Example 3)
[0155] A process was performed in the same manner as in Example 1 except that a 2,3-dihydroxynaphthalene solution in which 2,3-dihydroxynaphthalene was dissolved in 50 parts by weight of ethanol was used instead of the coating solution of Example 1.
[0156] (Comparative Example 4)
[0157] The processes were performed in the same manner as in Example 1, except that the mixture prepared in Example 1 was directly subjected to the heat treatment without the drying process.
[0158] (Experimental Example 1) Characteristic Analysis of Negative Electrode Active Material
[0159] The characteristics of each prepared negative active material were analyzed by performing X-ray diffraction (XRD) analysis, transmission electron microscopy (TEM), and Raman spectroscopy analysis experiments.
[0160] Figure 1 . The XRD analysis results of the negative electrode active materials manufactured according to Comparative Examples 1 and 2 and Example 1 are shown in FIG.
[0161] like Figure 1 As shown in , it was confirmed that the XRD patterns of Example 1 and Comparative Example 2 on which the carbon coating layer was formed were almost similar to the XRD pattern of Comparative Example 1 not including the carbon coating layer, and thus it was found that the crystal structure of silicon oxide as the core material was not affected by the formation of the carbon coating layer.
[0162] Figure 2 is a diagram showing TEM images of negative electrode active materials manufactured according to Comparative Examples 1 and 2, and Example 1.
[0163] like Figure 2 As shown in the TEM image of , it was confirmed that a carbon coating layer (red dot region) was formed on the silicon oxide core in the negative electrode active materials of Comparative Example 2 and Example 1. It was confirmed that the thickness of the carbon coating layer contained in the negative electrode active materials of Comparative Example 2 and Example 1 was formed to be 10 nm and 12 nm, respectively, and it was observed that the thickness uniformity in Example 1 was better than that in Comparative Example 2.
[0164] Although not shown in the drawings, it was observed that a carbon coating layer was formed on all the negative electrode active materials of Examples 2 to 4 and Comparative Examples 3 and 4, and it was confirmed that the average thickness of the formed carbon coating layer was 15 nm, 23 nm, 29 nm, 11 nm, and 11.5 nm, respectively. Regarding the thickness uniformity of the formed carbon coating layer, it was observed that the carbon coating layer included in the negative electrode active materials of Examples 2 to 4 had excellent thickness uniformity as in Example 1, but Comparative Examples 3 and 4 had relatively deteriorated thickness uniformity.
[0165] In addition, the carbon content contained in each negative electrode active material was measured by CS elemental analysis, and the results are summarized in the following Table 1:
[0166] [Table 1]
[0167] Carbon, wt% Comparative Example 1 0 Comparative Example 2 3.5 Example 1 2.7 Example 2 5.8 Example 3 8.6
[0168] Figure 3 (a) and Figure 3 (b) is a graph showing Raman spectra measured for each of the carbon coating layers included in the negative electrode active materials of Comparative Examples 1 and 2 and Examples 1 to 3, and results of Raman spectra showing deconvoluted peaks fitted from the measured Raman spectra.
[0169] like Figure 3 As shown in (a), since all negative electrode active materials of Comparative Example 2 and Examples 1 to 3 except Comparative Example 1 include a carbon coating layer, a peak at 1250 cm -1 Up to 1650cm -1 within the wave number range.
[0170] In reference Figure 3 When (b) is reviewed in detail, it is found that the peak center of the negative electrode active materials of Comparative Example 2 and Examples 1 to 3 is located at 1350±20cm -1 The central peak intensity of the D1 band in the wave number range I D1 , the peak center is located at 1500±10cm -1 The central peak intensity of the D3 band in the wave number range of I D3 The center of the peak is located at 1580±20cm -1 The central peak intensity of the G band in the wave number range of I G different.
[0171] First, in the I D1 with I G The ratio between D1 / I G, hereinafter referred to as R1), the R1 value of Comparative Example 2 is 1.26, indicating that the central peak intensity of the D1 band displayed by the disorder of sp2 carbon is higher than the central peak intensity of the G band, while the R1 values of Examples 1 to 3 are 1.00, 0.98 and 0.95, respectively, indicating that the central peak intensity of the D1 band is almost similar to the central peak intensity of the G band.
[0172] In addition, in the I D3 with I G The ratio between D3 / I G , hereinafter referred to as R2), it was confirmed that the R2 value of Comparative Example 2 was 0.36, while the R2 values of Examples 1 to 3 were 0.55, 0.54 and 0.57, respectively, which was different from the R2 value of Comparative Example 2.
[0173] Although not shown in the drawings, the R1 value and the R2 value of Example 4 were confirmed to be 0.91 and 0.60, respectively, and the R1 value and the R2 value of Comparative Example 3 were confirmed to be 1.29 and 0.32, respectively, similar to Comparative Example 2.
[0174] Subsequently, the surface chemical properties of Example 1 and Comparative Examples 1 and 2 were compared and analyzed using X-ray photoelectron spectroscopy (XPS).
[0175] Figure 4 (a) Figure 4 (b) and Figure 4 (c) is a graph showing high-resolution Si 2PXPS spectra including deconvoluted peaks corresponding to silicon having oxidation numbers of 0, 1, 2, 3, and 4 for the negative electrode active materials of Example 1 and Comparative Examples 1 and 2, respectively.
[0176] Reference Figure 4 (a) Figure 4 (b) and Figure 4 (c), it was found that the negative electrode active materials of Example 1 and Comparative Examples 1 and Comparative Examples 2 included deconvolution peaks corresponding to silicon with oxidation numbers of 1, 2, 3 and 4 showing maximum intensity values at binding energies of 101eV, 102eV, 103eV and 104eV, respectively, and a deconvolution peak corresponding to silicon with oxidation number 0 showing a maximum intensity value in the binding energy range of 99eV to 100eV, and the atomic percentages of silicon with different oxidation numbers are summarized in the following Table 2.
[0177] [Table 2]
[0178]
[0179] As shown in Table 2, it was confirmed that the silicon with an oxidation number of 4 of Example 1 was 41.6 at%, which was significantly higher than that of Comparative Example 1 (15.5 at%) and Comparative Example 2 (22.6 at%). In addition, when comparing the ratio (A4 / A1) of the atomic percentage (A4) of silicon with an oxidation number of 4 to the atomic percentage (A1) of silicon with an oxidation number of 1, Example 1 was confirmed to have a value of 8.66, while Comparative Example 1 and Comparative Example 2 were confirmed to have values of 1.06 and 3.65, respectively.
[0180] Figure 5 (a) and Figure 5 (b) are graphs showing high-resolution C1s XPS spectra including deconvoluted peaks of the negative electrode active materials of Example 1 and Comparative Example 2, respectively.
[0181] like Figure 5 (a) and Figure 5 As shown in (b), the deconvoluted peaks show that carbon includes sp 2 Bond structure (CC; 284.3 eV) and sp 3 bond structures (CO, C=O, and OC=O; 285.5 eV, 286.8 eV, and 288.7 eV), and the atomic percentages of carbons having each of these bond structures are summarized in Table 3 below.
[0182] [Table 3]
[0183]
[0184] As summarized in Table 3, it was found that 2 The carbon with a bond structure is 67.9 at% in Example 1 and 61.9 at% in Comparative Example 2. 2 The negative electrode active material of Example 1 of the carbon of the bond structure can improve the conductive property on the surface of the negative electrode active material.
[0185] In addition, when comparing the ratio of the content (at%) of carbon having a CC bond structure to the content (at%) of carbon having an OC═O bond structure having the highest binding energy, Example 1 was 12.6, while Comparative Example 2 was 8.6, and the two were found to be significantly different.
[0186] (Experimental Example 2) Characteristics Analysis of Secondary Batteries Containing Each Negative Electrode Active Material
[0187] In order to evaluate the influence of the difference in the crystal characteristics (Raman characteristics) of the carbon coating layer formed on the silicon oxide core on the characteristics of the secondary battery, each of the negative electrode active material, denka black, carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) was mixed in distilled water at a weight ratio of 6:2:1:1 to prepare a negative electrode active material slurry, and then the prepared negative electrode active material slurry was coated on one surface of the copper current collector with a thickness of 50 μm and dried. After drying, it was punched into a diameter of 14 mm to manufacture a negative electrode.
[0188] A coin-type half-cell was prepared by using lithium metal as a counter electrode, inserting a polyolefin separator between the negative electrode and the lithium metal, and then injecting an electrolyte solution. At this time, the electrolyte solution was an electrolyte solution in which 1M LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) at a volume ratio of 1:1.
[0189] The charge and discharge characteristics of coin-type half cells including the negative electrode active materials of Comparative Examples 1 and 2 and Example 1 were compared and analyzed.
[0190] Figure 6 (a) and Figure 6 (b) is a graph showing the results of charge and discharge cycle life characteristics and rate performance, respectively. At this time, the cycle life experiment was performed for 100 cycles with charging and discharging at a constant current of 1C as one cycle, and the rate performance was analyzed in turn every 5 cycles under different current density conditions of 0.2C, 0.4C, 1C, 2C, 4C, 10C, 20C and 0.2C.
[0191] Reference Figure 6 (a), the capacity retention rate of the coin-type half-cell containing the negative electrode active material of Example 1 after 100 charge and discharge cycles is about 97%, and considering the capacity retention rate of Comparative Example 1 (about 48%) and the capacity retention rate of Comparative Example 2 (about 88%), it is confirmed that Example 1 has significantly excellent cycle life characteristics.
[0192] Although not shown in the accompanying drawings, it is confirmed that the cycle life characteristics of the coin-type half-cells containing the negative electrode active materials of Examples 2 and 3 are also shown to be similar to those of Example 1, and the capacity retention rate of the coin-type half-cells containing the negative electrode active materials of Example 4 is about 93%, while the capacity retention rates of the coin-type half-cells containing the negative electrode active materials of Comparative Examples 3 and Comparative Examples 4 are about 82% and about 89%, respectively, which are inferior to the cycle life characteristics of the coin-type half-cells containing the negative electrode active materials of Examples 1 and 4.
[0193] It was thus found that the Raman characteristics of the above-mentioned negative electrode active material and the uniform carbon coating layer formed on the surface of the negative electrode active material affect the characteristics of the secondary battery.
[0194] like Figure 6 As shown in (b), it was confirmed that the rate performance also showed similar results as the charge and discharge cycle life characteristics.
[0195] In particular, the discharge capacity retention rate of the coin-type half-cell containing the negative electrode active material of Example 1 was about 83% even at a high rate of 20C, and it was observed that Example 1 showed significantly excellent rate performance compared with the discharge capacity retention rates of Comparative Examples 1 and 2 (about 72%).
[0196] In the above, although the present invention has been described by specific matters and specific exemplary embodiments, they are provided only to assist the overall understanding of the present invention. Therefore, the present invention is not limited to the exemplary embodiments, and those skilled in the art to which the present invention belongs can make various modifications and changes according to this specification. Therefore, the spirit of the present invention should not be limited to the above-mentioned exemplary embodiments, and the attached claims and all modifications identical or equivalent to the claims are intended to fall within the scope and spirit of the present invention.
Claims
1. A negative electrode active material comprising: a core comprising a porous silicon-based material; and a coating layer comprising amorphous carbon coated on a surface of the core, Wherein, the coating layer satisfies the following relation 1: (Equation 1) 1 <R1 / R2<3, Where R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band is G The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength at 1350±20cm -1 The G band has a peak center located at 1580±20cm -1 The peak center is within the wave number range of 1500±10cm, and the D3 band has a peak center located at 1500±10cm -1 The peak center within the wavenumber range.
2. The negative electrode active material according to claim 1, wherein The amorphous carbon is obtained from a resin having a repeating unit including an arylene group.
3. The negative electrode active material according to claim 2, wherein The resin has a repeating unit including one or more phenolic hydroxyl groups.
4. The negative electrode active material according to claim 3, wherein The resin includes a hydroxyl group equivalent of 150 g / eq to 300 g / eq.
5. The negative electrode active material according to claim 1, wherein R1 is 0.9 to 1.
05.
6. The negative electrode active material according to claim 1, wherein R2 is 0.5 to 0.
6.
7. The negative electrode active material according to claim 1, wherein The silicon-based material includes at least one material selected from silicon (Si), silicon oxide (SiO x (0 < x ≤ 2)), silicon alloy, or a combination thereof.
8. The negative electrode active material according to claim 7, wherein The silicon-based material contains 30 at % or more of silicon having an oxidation number of 4 in a Si 2P XPS spectrum of the negative electrode active material, and the Si 2P XPS spectrum includes deconvoluted peaks corresponding to silicon having oxidation numbers of 0, 1, 2, 3, and 4.
9. The negative electrode active material according to claim 8, wherein The silicon-based material satisfies the following relation 2: (Equation 2) A4 / A1≥4, Wherein, in the Si 2P XPS spectrum of the negative electrode active material, A4 is the atomic percentage of silicon having an oxidation number of 4, and A1 is the atomic percentage of silicon having an oxidation number of 1.
10. The negative electrode active material according to claim 1, wherein The coating layer has a thickness of 5 nm to 30 nm.
11. The negative electrode active material according to claim 1, wherein The core has an average diameter of 0.1 μm to 50 μm. 12 . A negative electrode for a secondary battery comprising the negative electrode active material according to claim 1 .
13. A method for producing a negative electrode active material, the method comprising: a) preparing a coating solution including a resin having a repeating unit including an arylene group and a solvent for forming a coating layer including amorphous carbon; b) preparing a first mixture of porous silicon-based powder in the coating solution; and c) drying the first mixture and then subjecting it to a heat treatment.
14. The method for producing a negative electrode active material according to claim 13, wherein: The coating solution has a viscosity of 5 cP to 200 cP.
15. The method for producing a negative electrode active material according to claim 13, wherein: The first mixture includes the coating solution and the silicon-based powder in a weight ratio of 1:8 to 1:
15.
16. The method for producing a negative electrode active material according to claim 13, wherein: The resin included in the coating solution has a repeating unit including one or more phenolic hydroxyl groups.
17. The method for producing a negative electrode active material according to claim 13, wherein: The heat treatment of c) is performed under an inert gas atmosphere at a temperature of 900° C. to 1100° C.
18. The method for producing a negative electrode active material according to claim 13, wherein: The following unit processes are performed one or more times using the product obtained after the heat treatment in c), The unit process comprises: b-1) preparing a second mixture of the product in the coating solution; and c-1) drying the second mixture and then subjecting it to a heat treatment.
19. The method for producing a negative electrode active material according to claim 18, wherein: In the first coating layer of the product obtained after c) to the Nth coating layer of the product obtained by performing the unit process n times or more, the standard deviations of the R1 value and the R2 value of the first coating layer to the Nth coating layer are respectively less than 0.1, Where R1 is the central peak intensity I of the D1 band D1 The central peak intensity of the G band is G The ratio (I D1 / I G ), and R2 is the central peak intensity I of the D3 band D3 The central peak intensity of the G band is G The ratio (I D3 / I G ), in the Raman spectrum, the D1 band has a wavelength at 1350±20cm -1 The G band has a peak center located at 1580±20cm -1 The peak center is within the wave number range of 1500±10cm, and the D3 band has a peak center located at 1500±10cm -1 The peak center within the wavenumber range.